Smart Frontal Safety System for Automobiles. Issue 1 (July 2021) - Govardhan, Y.S.; Sai, Doodi Maheedar; Sakthivel, G; Raghukiran, N; Saravanakumar, D
Abstract: The focus of this work is to develop a new safety system in addition to reduce accidents for innocents in automobiles. When confronted with an accident, the only safety measure which we bet our lives on is "airbags". In several cases, airbags alone may not be able to completely protect the passengers in the vehicle due to the high magnitude of the impact. In the present work, a new safety upgrade will be modeled in vehicles to absorb the sudden frontal impacts while in motion. The ultrasonic sensors are placed in the front portion of the vehicle which is set to propagate and receive ultrasonic waves while moving. The change of distance from the sensor to the obstacle is monitored continuously and in the event of an emergency, the frontal safety system in the vehicle gets activated. In such an event, the bumper or a metallic formed plate is actuated forward to a certain distance and upon striking the obstacle, the impact force is then reduced by shock absorbers or springs provided in the safety system. Hence, the impact transmitted to the passengers inside the vehicle is less when compared to the direct impact.